Fosamine ammonium impacts on the targeted invasive shrub Rhamnus cathartica and non-target herbs. (5th September 2020) - Schuster, Michael J.; Bockenstedt, Paul; Wragg, Peter D.; Reich, Peter B.
Abstract: Fosamine ammonium (Krenite ® ) is a foliar herbicide that primarily targets woody plant species; however, formal evaluations of its efficacy and potential for non-target impacts are scarce in the literature. The few tests of fosamine ammonium that exist focus primarily on its use in open environments, and the value of fosamine ammonium in controlling invasive understory shrubs is unclear. Here, we test the impact of fosamine ammonium on invasive common buckthorn ( Rhamnus cathartica L.) and co-occurring herbaceous plants across six forest sites in Minnesota, USA. Rhamnus cathartica treated with fosamine ammonium had a 95% mortality rate, indicating high efficacy of fosamine ammonium for use against R. cathartica . Non-target impacts varied between forbs and graminoids such that forb cover was reduced by up to 85%, depending on site, whereas graminoid cover was sparse and impacts of fosamine ammonium on graminoids were unclear. These results indicate that while fosamine ammonium can provide effective control of R. cathartica and other understory shrubs, there is potential for significant non-target impacts following its use. We therefore suggest that land managers carefully consider the timing, rate, and application method of fosamine ammonium to achieve desired target and non-target impacts.